Biological Control in Latin America and the Caribbean: Information Sources, Organizations, Types and Approaches in Biological Control - van Lenteren, Joop C.; Bueno, Vanda H. P.; Gabriela Luna, M.; Colmenarez, Yelitza C. [UNESP]; VanLenteren, J. C.; Bueno, VHP; Luna, M. G.; Colmenarez, Y. C. (Cabi Publishing-c A B Int, 2020)
Biological control with arthropod natural enemies and microbial control agents has been applied since the year 1895 in Latin America and the Caribbean and is currently used on a very large scale. Sources about the history and current situation of biocontrol in this region were not easy to trace and are, therefore, presented in this chapter. Next, organizations working on biocontrol in this region are listed. This is followed by a description of natural, conservation, classical and augmentative biocontrol with some regional examples. Then, an approach to find, evaluate and use biocontrol agents is sketched, as guidance for research projects. Often, tens to a hundred biocontrol candidates are found in association with a pest. A well organized research approach using evaluation criteria allows for quick exclusion of unsuitable or problematic candidate species. Biocontrol research has limited funding and early elimination of poor candidates results in spending more money on promising candidates. Regulations concerning import and release of agents that have been implemented during the past 30 years are summarized. Effects of these regulations are that prospecting for exotic natural enemies is now very difficult and that fewer new biocontrol agents have become available. Finally, the structure of the book is explained.